The Impact of Business Incubation Programmes on Start-up Success and Economic Growth in Indonesia - Loso Judijanto; Widyatmoko Widyatmoko (Westscience Press, 2024)
This study investigates the impact of business incubation programs on start-up success and economic growth in Indonesia. Using a quantitative approach, data were collected from 80 start-ups through a structured questionnaire utilizing a 5-point Likert scale. The data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results reveal that business incubation programs significantly enhance start-up success, with a positive effect on the overall success of start-ups. Furthermore, successful start-ups contribute to economic growth by generating jobs, fostering innovation, and promoting market expansion. The findings underscore the importance of business incubation as a catalyst for entrepreneurial success and economic development. The study suggests that strengthening business incubation programs should be a priority for policymakers in Indonesia to promote a thriving start-up ecosystem and sustain long-term economic growth.